Amish (Rural) vs. non-Amish (Urban) Infant Fecal Microbiotas Are Highly Diverse and Their Transplantation Lead to Differences in Mucosal Immune Maturation in a Humanized Germfree Piglet Model - Dhakal, Santosh; Wang, Lingling; Antony, Linto; Rank, Jennifer; Bernardo, Pauline; Ghimire, Shristi; Bondra, Kathy; Siems, Christina; Lakshmanappa, Yashavanth Shaan; Renu, Sankar; Hogshead, Bradley; Krakowka, Steven; et al. (Frontiers in Immunology, 2019)
Gut microbiome plays a major role in the development of the immune system in mammals. In this study, we comparatively examined the fecal microbiomes of Amish (rural) and non-Amish (urban) infants and investigated how they could affect the mucosal immune maturation in germ-free piglets that were humanized with the two types of infant fecal microbiota. Differences in microbiome diversity and structure were noted between the two fecal microbiotas. The fecal microbiota of the urban infants had a greater relative abundance of Actinobacteria and Bacteroidetes, while that of the rural counterparts was dominated with Firmicutes, particularly the genus Prevotella. The fecal microbiotas of the urban and the rural infants were successfully transplanted into germ-free piglets, and the diversity and structure of the microbiota in the transplanted piglets remained the same at phylum level but not at the genus or subgenus level. Principal coordinate analysis (PCoA) revealed distinct microbiota structure in the intestines of the transplanted piglets. Functional features of the gut metagenome of the two groups of humanized piglets showed distant clustering on PCoA plot with high variance, associated with differences in the frequency of different mucosal immune cells in the intestines of piglets. Some colonized bacterial genera were correlated with the frequency of important lymphoid and myeloid immune cells in the ileal submucosa and mesenteric lymph nodes, both important for mucosal immune maturation. Metagenomic analysis also revealed differences in functional genes between the two groups of infant fecal microbiota and the respectively humanized piglets, with the urban infant fecal microbiota showing a greater predominance of serine aminopeptidases and dipeptidyl peptidases, while that of the rural counterparts increasing the predominance of 23 other functional gene features. Overall, this study demonstrated that transplantation of diverse infant fecal microbiota into germ-free piglets recapitulates the differences in the gut microbiota structure between rural and urban infants. Thus, fecal microbiota transplantation to germ-free piglets could be a useful large animal model system for elucidating the impact of gut microbiota on the mucosal immune system development. Future studies will focus on determining the additional advantages of the pig model over the rodent model.